Fiduciaries in the administration of the deceased's estate: the two distinct capacities of personal representatives and trustees - Halim, Akmal Hidayah; Mohd Noor, Nor Azlina (CLJ Legal Network Sdn Bhd, 2016)
The office of personal representative in the administration of a deceased’s estate requires a personal representative who must at the utmost ensure himself to have a solemn understanding of his duties and obligations. The personal representative must act with the highest degree of trustworthiness and good faith in discharging his office. However, in the process of estate administration, one question that has nagged the office of personal representative is that what should be the two distinct capacities of personal representative and trustee since the expression of trustee under the Malaysian Trustee Act 1949 includes the duties incidental to the office of a personal representative. The question is relevant because the role of a personal representative is quite distinct from that of a trustee and is subject to different legal framework and liability. Hence, this paper seeks to examine the legal position of a personal representative and to identify the line separating the duties of a personal representative from his duties as a trustee. For this purpose, the paper analyses relevant statutory provisions as provided by the Probate and Administration Act 1959 and the Trustee Act 1949. An analysis of the decided cases is also made to identify the distinction between the offices of a personal representative to that of a trustee in the administration of the deceased’s estate. The paper concludes that there is no objective test as to when and how a personal representative becomes a trustee since a person may be a personal representative in respects of certain assets and trustee in respect of others. The two distinct capacities however, would be significant in determining the available remedies to the estate beneficiaries in cases where these fiduciaries fail to discharge their duties accordingly.